Utilization of Coconut Shells as a Source of Graphene Nanosheets Fe/N-GNS for Environmentally Friendly Primary Battery Electrodes - Giyanto; Affi, Jon; Gunawarman; Handayani, Murni; Yetri, Yuli (Program Studi Teknik Mesin Universitas Pamulang, 2026)
The research on the performance of carbon (C)/d-orbital metals (graphite/graphene, graphene/N-graphene, graphite/Fe-graphene, graphite/Fe-N-graphene, and graphene/Fe-N-graphene) in primary battery electrode systems was carried out using a simple technology by mixing coconut shell powder with N and Fe. The purpose of this study was to determine the preparation method of Fe/GNS and Fe/N-GNS electrodes and to evaluate the performance of the electrolyte on electron distribution in Fe/GNS and Fe/N-GNS electrodes as primary battery anodes based on electrical conductivity values. This research was conducted as a laboratory experimental study. GNS and N-GNS were synthesized using a modified Hummers method, while Fe/GNS and Fe/N-GNS electrodes were synthesized using the impregnation method. GNS, N-GNS, Fe/GNS, and Fe/N-GNS after electrolyte combination were characterized using SEM–EDX and a multimeter, respectively. The SEM–EDX results at 170 °C and 500–600 °C showed a folded and wrinkled graphene structure with dispersed Fe (5.3 wt% by EDX), dominated by C and O. The addition of Fe–NH₃ acted as a catalyst to form more regularly structured graphite. The DHL test showed the highest electrical conductivity ( 51,400 at 40 V) for Fe-N-GNS samples synthesized at 170 °C and 600 °C, which were identified as the most optimal synthesis conditions.